Integrating Science and Religion in the Era of Globalization: A Study of the Islamization of Knowledge through the Integrated Islamic School Model - Syafe’i, Syafe’i; Noviani, Dwi (International Journal on Advanced Science, Education, and Religion, 2025)
Globalization and advances in information technology have brought significant changes to the world of education, including Islamic education. Rapid modernization demands that Islamic educational systems adapt while preserving their core Islamic values. This study aims to analyze the process of Islamization of knowledge within the context of globalization and to examine the role of Integrated Islamic Schools (Sekolah Islam Terpadu/SIT) as an educational model that integrates general and religious knowledge. Employing a qualitative approach through library research, this study reviews relevant literature on the Islamization of knowledge, the history of Islamic education, and the development of the SIT model in Indonesia. The findings indicate that Integrated Islamic Schools emerged as a response to the long-standing dualism between religious and general education. The SIT model integrates the national curriculum with Islamic values through contextual, dialogic, and character-based learning approaches. Consequently, the Islamization of knowledge in the era of globalization can be realized through an educational design grounded in tauhid, oriented toward character formation, and adaptive to technological advancements